Homo interneticus jako analfabeta funkcjonalny w zakresie praw człowieka - Walat, Wojciech (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article discusses the problem of universal lifelong education, which is facing a truly difficult challenge today: how to go from the traditional to functional literacy of homo interneticus, who is convinced of and even believes only in the power of his smartphone connected to the Internet. Unfortunately, the modern man – homo interneticus – in the sense of his unlimited power flowing from the Internet, remains a satisfied functional illiterate also in the sphere of his rights.
Homo interneticus as a functional illiterate in the field of human rights
Artykuł powstał w oparciu o platformę badawczą Pracowni Lifelong Learning, Laboratorium Zagadnień Społeczeństwa Informacyjnego w Centrum Innowacji i Transferu Wiedzy Techniczno-Przyrodniczej Uniwersytetu Rzeszowskiego.
Keywords: homo interneticus; universal lifelong learning; illiteracy; functional illiteracy; human rights